A Bibliometric Analysis of Green Skills Research in Vocational Education: 2018-2022 - Fitriyanto, Muhammad Noor; Wagiran, Wagiran; Zannah, Fathul; Novian, Dian; Mansur, Hamsi (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
Green skills (GSs) have become one of the important strategies for achieving sustainable development. It can make the environment effective for social and economic development. The aim of this research is to reveal data on the evolution and development of green skills and trends in the development of green jobs throughout the world. This research uses R Studio and Bibliometrix to analyze 198 papers related to green skills in green jobs published from 2018 to 2022 in the Scopus database using Bibliometrix and visualization mapping methods. The results show a substantial increase in the number of studies GSs in recent years, with the focus area in European and American countries leading this research. Aspects of Will, manufacturing and Energy, and Journals of Green Environmental Management are the first three journals cited in the study of GSs. Studying the cited literature together on environmentally friendly skills includes, among other things, the relationship between other skills and ecosystems with human good health, green construction, evaluation and green management of environmentally friendly competencies, and analysis of specific aspects of environmentally friendly skills. The results of the analysis of green skills grouping keywords show that there is research that concentrates on green skills in the fields of education, ecosystem services, climate change, and biodiversity protection. In conclusion, this research provides a reference for future studies of green skills necessary for the development of a sustainable educational environment, such as a multidisciplinary approach, adaptation of new technologies, partnerships with sustainable technology green industries, and environmental awareness.